797 Significant anti-tumor activity of HBI-8000, a class I histone deacetylase inhibitor (HDACi) in combination with nivolumab (NIVO) in anti-PD1 therapy-naïve advanced melanoma (TN-Mel). (10th December 2020) - Khushalani, Nikhil; Brohl, Andrew; Markowitz, Joseph; Bazhenova, Lyudmila; Daniels, Gregory; Yeckes-Rodin, Heather; Fu, Siqing; McCormick, Lori; Kurman, Michael; Gillings, Mireille; Lee, Gloria; Eroglu, Zeynep
Abstract : Background: Anti-PD1 based therapy has been the mainstay of treatment for advanced melanoma for several years. HBI-8000 is a Class I selective oral HDACi with immunomodulatory effects including enhanced cell-mediated toxicity, enhanced tumor infiltration by cytotoxic T-cells and reduced tumor infiltration by T-regulatory cells. In a phase 1b/2 trial in melanoma, kidney cancer and non-small cell lung cancer, the recommended phase 2 dose of HBI-8000 was determined to be 30mg orally twice weekly (BIW) combined with nivolumab administered at the approved dosing schedule (JITC 2018;P346). This report describes the tolerability of this combination in all enrolled melanoma patients, and efficacy in the expansion cohort of anti-PD1 TN-MEL. Methods: Patients with unresectable or advanced melanoma and measurable disease, of ECOG performance status 0-1, and with adequate hematologic and biochemical parameters were enrolled. Treated brain metastases not requiring steroids were permitted. Tumor response was assessed by RECIST v1.1 and iRECIST with staging every 8 weeks; treatment continued for 24 months, disease progression or unacceptable toxicity. Data cut-off was Jan 31, 2020 for the reported analyses Results: Forty-nine patients (32 anti-PD1 naïve, 17 with prior anti-PD1 therapy) were treated with HBI-8000 (47 patients at 30 mg BIW; 2 patients at 40mg BIW in Phase 1b) in combination with nivolumab. The median age was 63 years (range 28-84); 57% were male. In the anti-PD1 naïve cohort, most (30/32) had normal LDH. The most common all grade treatment related adverse events (AEs) included fatigue (n=25), diarrhea (n=24), abdominal pain (n=14), and lymphopenia (n=13). Although HBI-8000 related thrombocytopenia (n=25) and neutropenia (n=15) were common, clinically significant bleeding or febrile neutropenia were not observed. The most frequent >/= G3 AEs related to HBI-8000 were hypophosphatemia (n=7), neutropenia (n=4), thrombocytopenia (n=3) and lymphopenia (n=2). Twelve patients discontinued treatment for AEs. Among 31 anti-PD1 naïve patients evaluable for response, there were 23 objective responses (4 CR, 19 PR; ORR 74%), 5 stable disease (disease control rate 90%), and 3 progressive disease. Median time to response was 1.9 months. At a median follow-up for this cohort of 8.9 months (range, 0.9-35.5 months), the median duration of response and median progression-free survival have not been reached. Conclusions: The combination of HBI-8000 and nivolumab is well tolerated and demonstrates very encouraging efficacy in patients with anti-PD1-naïve advanced melanoma. Follow-up to assess durability of response is ongoing, and further investigation of this promising combination is planned. Trial Registration: NCT02718066 Ethics Approval: The study was approved by participating study sites' Institutional Review Boards and the Sponsor has conducted the trial in full compliance with all GCP and FDA regulations.